Análisis del impuesto predial unificado y su recaudo en el municipio de Tasco Boyacá de los años 2016 a 2020 (2021)
This research is aimed at analyzing the unified property tax and its collection in the municipality of Tasco Boyacá in the periods from 2016 to 2020, taking into account the elements and principles established in the municipal tax statute and considering the relevance of the tax for municipal development; so it will be of great use to both taxpayers and the mayor's office.